2007
DOI: 10.1002/lt.21211
|View full text |Cite
|
Sign up to set email alerts
|

Morbid obesity with one or more other serious comorbidities should be a contraindication for liver transplantation

Abstract: The prevalence of obesity is increasing in the United States and the rest of the world. The World Health Organization reported last year that over a billion people in the world are obese, surpassing 600 million malnourished people. In some ways, this is a reassuring sign that we are combating poverty in the world, but the impact of obesity on long-term morbidity, mortality, and utilization of health resources is similar or higher. [1][2][3][4][5] The reports from the Centers for Disease Control and the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…If obese patients with 1 or more other serious comorbidities are felt to be poor candidates for transplantation, perhaps they should not be added to the waiting list. 31 If indeed as a community we feel that liver allografts should not be distributed to patients with excessive postoperative risk, we should consider expressing this as a formal change to our allocation policy rather than through informal practice patterns. …”
Section: Discussionmentioning
confidence: 98%
“…If obese patients with 1 or more other serious comorbidities are felt to be poor candidates for transplantation, perhaps they should not be added to the waiting list. 31 If indeed as a community we feel that liver allografts should not be distributed to patients with excessive postoperative risk, we should consider expressing this as a formal change to our allocation policy rather than through informal practice patterns. …”
Section: Discussionmentioning
confidence: 98%
“…In fact, the leading cause of graft loss shifted over the last few decades from graft rejection to patient death due to cardiovascular disease [9], indicating that obesity-related co-morbidities, such as type 2 diabetes (T2DM) and hypertension (HTN), and their association with higher mortality may be important predictors of outcome following transplantation. In addition, many centers have limited provision of transplantations to patients with BMI o35 kg/m 2 while others consider BMI between 35 and 40 kg/m 2 as a relative contraindication for transplantation [10,11]. With increasing evidence that obesity leads to poor outcomes in transplantation patients, strategies to reduce risk are being investigated.…”
mentioning
confidence: 99%
“…3-8 For the latter, there has been continued controversy regarding the association of recipient BMI and posttransplant outcomes, with multiple studies reporting conflicting results. Some studies found that LT recipients with extremely low BMI were associated with a higher mortality risk 9 ; some studies found that obese patients or an elevated BMI were associated with a higher mortality risk, 3,4,6,9 whereas others did not find this association in obese groups.…”
mentioning
confidence: 99%